Marke-tugs is the new sound of marke-ting a case study of Filipino fans' Facebook page as a consumer empowerment through the internet - Acaylar, Ea Gesika Maglanque 1991-; Santos, Josefina M.C. (2012)
"This Undergraduate Thesis examines the Consumer Empowerment exhibited by the Millennials through creation of a Facebook (Fan) Page. The Facebook page, Tugs Page, was inspired with the Television Commercial "Tugs" od Selecta Cornetto's first marketing campaign, the "Bente" campaign. The success of Tugs page is incomparable compared to the official Facebook Page of Selecta Cornetto. This phenomenon has exhibited Consumer Empowerment through various themes and has been more supported by the Millennials. Using grounded theory, to identify how the empowerment happened virtually through participant observation, interview and a Focus Group Discussion to pinpoint the source of consumer empowerment of the said phenomenon. In the process, consumer empowerment was realized to be absent within the consciousness of the Millennials but the need for it have brought them to resist being just passive audiences. This study revealed themes that, although unconsciously created, are consistent and have drawn attention from other Millennials, unconsciously seeking the same consumer empowerment."
Vita.
Undergraduate thesis (A.B. Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Facebook; Internet marketing